GEOMETRIC DESIGNS IN THE INDIGENOUS ATTIRES OF THE BONTOC TRIBE: AN EVIDENCE OF “ETHNOMATHEMATICS” - Gayagay, Glen (IJRDO -JOURNAL OF MATHEMATICS, 2021)
This paper primarily intended to describe and discuss the geometric designs in the indigenous attires specifically in the lufid, wakhes, and wanes of the Bontoc Tribe in Mountain Province. It employed descriptive ethnographic study approach, a semi-structured interview guide and document analysis of the existing geometric designs the 3 indigenous attires. Results show that the geometric designs that can be found in the indigenous attires applying sinnawed method of weaving are matmata, tiktiko, tagtakho, kalasag, tufay, pinang, u-uweg, fatawer, sokyong faniyas, and sabsabong. Each design may be classified as pinagpagan, kulibangbang, and kinaut. The designs generally represent an object in the environment and represent some cultural beliefs and traditions of the ancestors of the Bontoc tribe. The geometric designs are associated to elements of lines and shapes. The creativity of the weavers with the rapid growth of technology and the development of the tourism industry of the Mountain Province made it possible for the weavers to make same variations on the designs. Combinations of these elements of shape resulted to these variations. At a practical level, the findings will provide valuable resources to the teachers of the Bontoc tribe as they teach mathematics through their mother tongue. The findings may serve as additional information on how and why mathematics specifically geometry and indigenous knowledge and practices are interrelated.